Wicked appetite [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Lizzy and Diesel novels., 2010)
Life in Marblehead has had a pleasant predictability, until Diesel arrives. Rumor has it that a collection of priceless ancient relics representing the Seven Deadly Sins have made their way to Boston's North Shore. Partnered with pastry chef Lizzie Tucker, Diesel bullies and charms his way through historic Salem to track them down. The black-haired, black-hearted Gerewulf Grimorie is on the hunt for the relic representing gluttony. Caught in a race against time, Diesel and Lizzie soon find out that more isn't always better, as they battle Wulf and the first of the deadly sins.